Applicability of SPMSQ in illiterate outpatients in clinics: The validity and reliability of the Short Portable Mental Status Questionnaire. Issue 4 (4th July 2022) - kojaie-Bidgoli, Afsaneh; Fadayevatan, Reza; Sharifi, Farshad; Alizadeh-Khoei, Mahtab; Vahabi, Zahra; Aminalroaya, Reyhaneh
Abstract: Objectives: The Short Portable Mental Status Questionnaire is a brief cognitive tool designed to screen cognitive impairment in geriatric inpatients and outpatients. The validity and reliability of this tool have not been studied in Iran so far. Therefore, this study was conducted to assess the diagnostic properties of the SPMSQ for detection of cognitive disorders in elderly and determine an appropriate cutoff point based on respondents' level of education. Methods: This cross-sectional study was conducted through face to face interviews on a sample of 156 patients (≥60 years) referred to neurology and geriatric clinics of Ziaiyan hospital, Tehran University of Medical Sciences. Regarding the type of cognitive impairment, Participants were divided into two groups; those with cognitive disorders ( n = 96) and healthy ( n = 60). The level of literacy was also considered in each of the groups. Results: The Cronbach's alpha coefficient for the SPMSQ was 0.88. In terms of the concurrent validity, a correlation coefficient between SPMSQ and GDS was higher in the literate group compared to the illiterate patients, while in the illiterate group, the SPMSQ had a higher correlation with AMT compared to the other tools. Based on DSM-5, the cutoff point of SPMSQ was 4 in the illiterate elderly patients and the sensitivity and specificity of the tool were at 86.4 and 88.2%, respectively. However, in the literate patients, the cutoff point was 3 and the sensitivity and specificity were 83 and 93.7%, respectively. Also, two components, namely orientation and long-term memory/concentration were determined for the SPMSQ using the factor analysis. Conclusion: The Iranian version of SPMSQ has a favorable validity and reliability for diagnosing cognitive disorders and can be used for cognitive screening of illiterate older adults.